Measurements of the top-quark mass and the tt cross section in the hadronic τ+jets decay channel at sqrt[s] = 1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Arisawa, T; Artikov, A; Asaadi, J; et al. (2012)
We present the first direct measurement of the top-quark mass using tt events decaying in the hadronic τ+jets decay channel. Using data corresponding to an integrated luminosity of 2.2 fb(-1) collected by the CDF II detector in pp collisions at sqrt[s] = 1.96 TeV at the Fermilab Tevatron, we measure the tt cross section, σ(tt), and the top-quark mass, M(top). We extract M(top) from a likelihood based on per-event probabilities calculated with leading-order signal and background matrix elements. We measure σ(tt) = 8.8 ± 3.3(stat) ± 2.2(syst) pb and M(top) = 172.7 ± 9.3(stat) ± 3.7(syst) GeV/c(2).